Analysis of dynamic MR breast images using a model of contrast enhancement. - Hayton, P; Brady, M; Tarassenko, L; Moore, N (1997)
We describe a model of dynamic contrast enhancement in breast MRI designed to aid the radiologist in cases for which X-ray mammography is ineffective. The breasts are segmented from the image slices by a dynamic programming algorithm after morphological opening. A pharmacokinetic model has been derived to fit the rise in intensities after injection of a contrast agent, in a way that facilitates investigation of the effects of different models of bolus injection. The pharmacokinetic model is used in a modified Horn-Schunck algorithm to correct for motion effects during the seven minute acquisition period. The results show significant localization of tumours and enable discrimination of cancerous tissue. In particular, we illustrate the approach with an image that shows a carcinoma, whose appearance and localization are greatly improved by the registration algorithm.